2013
DOI: 10.1016/j.juro.2013.01.101
|View full text |Cite
|
Sign up to set email alerts
|

Urine Neutrophil Gelatinase-Associated Lipocalin as a Marker of Acute Kidney Injury After Kidney Surgery

Abstract: Purpose Evaluate uNGAL as a marker for AKI in patients undergoing PN to identify the preoperative clinical features and surgical factors during PN that are associated with renal injury as measured by increased uNGAL levels compared to controls. Methods Using RN and thoracic surgery patients as control groups, we prospectively collected and analyzed urine and serum of PN, RN, and thoracic surgery patients between April 2010 and April 2012. Urine was collected preoperatively and at multiple time points postope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
17
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 27 publications
3
17
1
Order By: Relevance
“…[16][17][18] Increased expression of these biomarkers was observed in our experiments, and KIM-1 was significantly elevated after IRI compared to off-clamp PN. This biomarker has been proven to be more sensitive than serum creatinine for AKI diagnosis and it may be a better method of evaluating renal function in the setting of IRI.…”
Section: Discussionsupporting
confidence: 69%
“…[16][17][18] Increased expression of these biomarkers was observed in our experiments, and KIM-1 was significantly elevated after IRI compared to off-clamp PN. This biomarker has been proven to be more sensitive than serum creatinine for AKI diagnosis and it may be a better method of evaluating renal function in the setting of IRI.…”
Section: Discussionsupporting
confidence: 69%
“…sCr and accompanying eGFR changes in diagnosis of AKI may frequently be missed out particularly when the opposite kidney is healthy (1) and thus could not predict the initial time of damage neither the degree of severity. sCr starts to increase when the kidney function decreases by 50% The detection of less damage in their study might be due to several factors, such as performing cold ischemia, which has a better kidney protection effect, in most patients during the renal artery clamping, and infusion of intraoperative mannitol (13). We conducted tumor resection using laparoscopic method and under the warm ischemia in all patients.…”
Section: Discussionmentioning
confidence: 99%
“…The sCr levels increase as early as 24-48 hours after the development of kidney injury. In this regard, researchers have used other specific biomarkers for identification of kidney injury to make early diagnosis (12)(13)(14). Neutrophil gelatinase-associated (NGAL) is a significant biomarker that has diagnostic and prognostic significance in early diagnosis of kidney ischemia-reperfusion injury.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…NGAL produced by renal cells is excreted in the urine and does not circulate in the blood . Therefore, many studies reporting changes in NGAL with acute kidney injury, kidney surgery, or renal ischaemia–reperfusion injury have analysed urinary NGAL (uNGAL) rather than (or in addition to) sNGAL . Several observational studies have evaluated uNGAL in kidney donors, but none have definitively reported how uNGAL relates to renal function of the living kidney donor .…”
Section: Introductionmentioning
confidence: 99%